AOSpine—Spine Trauma Classification System: The Value of Modifiers: A Narrative Review With Commentary on Evolving Descriptive Principles. Issue 1 (May 2019) - Divi, Srikanth N.; Schroeder, Gregory D.; Oner, F. Cumhur; Kandziora, Frank; Schnake, Klaus J.; Dvorak, Marcel F.; Benneker, Lorin M.; Chapman, Jens R.; Vaccaro, Alexander R.
Study Design: Narrative review. Objectives: To describe the current AOSpine Trauma Classification system for spinal trauma and highlight the value of patient-specific modifiers for facilitating communication and nuances in treatment. Methods: The classification for spine trauma previously developed by The AOSpine Knowledge Forum is reviewed and the importance of case modifiers in this system is discussed. Results: A successful classification system facilitates communication and agreement between physicians while also determining injury severity and provides guidance on prognosis and treatment. As each injury may be unique among different patients, the importance of considering patient-specific characteristics is highlighted in this review. In the current AOSpine Trauma Classification, the spinal column is divided into 4 regions: the upper cervical spine (C0-C2), subaxial cervical spine (C3-C7), thoracolumbar spine (T1-L5), and the sacral spine (S1-S5, including coccyx). Each region is classified according to a hierarchical system with increasing levels of injury or instability and represents the morphology of the injury, neurologic status, and clinical modifiers. Specifically, these clinical modifiers are denoted starting with M followed by a number. They describe unique conditions that may change treatment approach such as the presence of significant soft tissue damage, uncertainty about posterior tension band injury, or the presence of a critical disc herniation in a cervical bilateral facet dislocation. These characteristics are described in detail for each spinal region. Conclusions: Patient-specific modifiers in the AOSpine Trauma Classification highlight unique clinical characteristics for each injury and facilitate communication and treatment between surgeons.